Implementasi Metode Learning Vector Quantization Pada Aplikasi Penerjemah Huruf Hijaiyah Menggunakanan Pose Jari Tangan - Nada Fitria Nada Fitria; Suendri; Triase (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The challenge faced at SLB Negeri Autism Sumatra is how to teach education to deaf students so that they can lead normal daily lives and receive religious education according to their beliefs. Currently, the introduction of hijaiyah letters is still done manually by teachers, which causes less efficiency in the learning process because it depends on the individual skills of the teacher. In addition, learning materials for hijaiyah letters are difficult to find in the form of learning media, both in the form of books and electronic media. To overcome this problem, it is necessary to develop web-based applications using the Learning Vector Quantization (LVQ) method. This application will facilitate teachers and students of the Autistic Sumatran State SLB in learning hijaiyah letters by displaying the appropriate finger poses. With this application, it is hoped that the learning process can be carried out more efficiently and can be repeated as needed. The purpose of this study is to provide good religious education to deaf students at the Autistic Sumatran State SLB. This research is still in its early stages, but the hope is that it will yield positive results. Through this application, it is hoped that deaf students can learn hijaiyah letters independently and more easily, so that they can carry out their religious worship properly. The results of this study will be measured in the form of numbers or percentages to evaluate the effectiveness of the application in increasing the learning of hijaiyah letters in the Autism State SLB Sumatra